2017
DOI: 10.1142/s0218348x17500426
|View full text |Cite
|
Sign up to set email alerts
|

A Fractal Permeability Model Coupling Boundary-Layer Effect for Tight Oil Reservoirs

Abstract: A fractal permeability model coupling non-flowing boundary-layer effect for tight oil reservoirs was proposed. Firstly, pore structures of tight formations were characterized with fractal theory. Then, with the empirical equation of boundary-layer thickness, Hagen-Poiseuille equation and fractal theory, a fractal torturous capillary tube model coupled with boundary-layer effect was developed, and verified with experimental data. Finally, the parameters influencing effective liquid permeability were quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Limited efforts have been made in the literature to investigate the dynamic capillary pressure in a hydraulic fractured porous media, especially the experimental studies. Moreover, it is observed that tight rocks are associated with large boundary layer effect on fluid flow, and such phenomenon is also required to be considered when integrating the dynamic effect in these rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Limited efforts have been made in the literature to investigate the dynamic capillary pressure in a hydraulic fractured porous media, especially the experimental studies. Moreover, it is observed that tight rocks are associated with large boundary layer effect on fluid flow, and such phenomenon is also required to be considered when integrating the dynamic effect in these rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal dimension is the main tool to characterize the complex structure of the fractal object, and the introduction of which is the novelty of fractal theory. It can be easily noticed from existing fractal research that the relationship between the fractal dimensions of the research objects and other physical parameters is the focus of many studies [43,44].…”
Section: The Box-counting Methods and Fractal Dimensionmentioning
confidence: 99%
“…The geometry of a fracture network is related to the fractal controlling parameters, and the multi-level bifurcated geometry of a fractal fracture better represents fractures of different orders and branches. Fuyong et al [21,22] investigate fluid flow in fractal porous media and propose simulation method for the permeability of porous media based on the multiple fractal models.…”
Section: Introductionmentioning
confidence: 99%